Restrictive Cardiomyopathy Caused by Troponin Mutations: Application of Disease Animal Models in Translational Studies - Liu, Xiaoyan (Front Physiol, 2016)
Cardiac troponin I (cTnI) plays a critical role in regulation of cardiac function. Studies have shown that the deficiency of cTnI or mutations in cTnI (particularly in the C-terminus of cTnI) results in diastolic dysfunction (impaired relaxation) due to an increased myofibril sensitivity to calcium. The first clinical study revealing the association between restrictive cardiomyopathy (RCM) with cardiac troponin mutations was reported in 2003. In order to illustrate the mechanisms underlying the cTnI mutation caused cardiomyopathy, we have generated a cTnI gene knockout mouse model and transgenic mouse lines with the reported point mutations in cTnI C-terminus. In this paper, we summarize our studies using these animal models from our laboratory and the other in vitro studies using reconstituted filament and cultured cells. The potential mechanisms underlying diastolic dysfunction and heart failure caused by these cTnI C-terminal mutations are discussed as well. Furthermore, calcium desensitizing in correction of impaired relaxation in myocardial cells due to cTnI mutations is discussed. Finally, we describe a model of translational study, i.e., from bedside to bench and from bench to bedside. These studies may enrich our understanding of the mechanism underlying inherited cardiomyopathies and provide the clues to search for target-oriented medication aiming at the treatment of diastolic dysfunction and heart failure.